Dairy herd health [ - Green, Martin [ (Martin J.)] (CABI, 2012)
Dairy herd health is an important and universal topic in large animal veterinary practice and farming, covering both preventive medicine and health promotion. With the move towards large scale farming, the health of the herd is important as an economic nit and to promote the health of the individuals within it. This book will focus on diseases within herds, herd husbandry practices, youngstock management and environmental issues. Major diseases and conditions will be covered such as mastitis, lameness, nutrition, metabolic and common infectious diseases from a herd health perspective. It is suitable for veterinary practitioners and students, researchers and dairy industry personnel.